Apresentação PBCIB n.2, v.15, 2020 - Rodrigues Hermes de Araújo, Vania; Maria Freire, Isa; Henrique de Araújo Freire, Gustavo (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2023)
Apresentação PBCIB n.2, v.15, 2020